2012
DOI: 10.2174/1877944111202010054
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Toxicology of Aluminum in the Brain

Abstract: The chemical forms (species) of aluminum in blood plasma and brain extracellular fluid are considered, as they are the candidates for brain aluminum uptake and efflux. The blood-brain barrier is the primary site of brain aluminum uptake. The mechanism of brain uptake of aluminum transferrin, long thought to be mediated by transferrin-receptor mediated endocytosis, requires further investigation. Brain Al citrate uptake has been attributed to the sodium-independent Lglutamate/L-cystine exchanger system, system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 112 publications
2
66
0
6
Order By: Relevance
“…The present result might be attributed to the ability of Al to alter the blood brain barrier and produce marked changes in the cholinergic neurotransmission [49]. Al is well known as a potent brain cholinotoxin with slow accumulation rate [50,51].…”
Section: Discussionmentioning
confidence: 67%
“…The present result might be attributed to the ability of Al to alter the blood brain barrier and produce marked changes in the cholinergic neurotransmission [49]. Al is well known as a potent brain cholinotoxin with slow accumulation rate [50,51].…”
Section: Discussionmentioning
confidence: 67%
“…However, increased production of ROS was reported during Al exposure, which is attributed to electron leakage and increased electron chain activity [2,8]. Subsequently ROS attack most cell components including membrane lipids producing lipid peroxidation [115]. Therefore, oxidative stress can be hypothesized to be one of the contributing factors for Al-induced central nervous disorders [116].…”
Section: Controlmentioning
confidence: 99%
“…This was followed by many studies, some of which found a few-fold or smaller increase of the Al concentration in AD victim brains than in controls, and some which did not. Studies investigating an elevated level of Al in AD brain using microprobe techniques, such as energy dispersive (electron probe) X-ray microanalysis, secondary ion mass spectrometry, and laser microprobe mass spectroscopy which can quantify Al within a cell, NFT or SP, as well as Al-selective stains, have also produced mixed results (Yokel 2000). If Al is elevated in AD brain, it is not reflected in cerebrospinal fluid Al, which has generally not been found to be elevated (Kapaki et al 1993).…”
Section: Evidence For and Against A Role Of Aluminum In Alzheimer's Dmentioning
confidence: 99%